Sex disparities in the assessment and outcomes of chest pain presentations in emergency departments. Issue 2 (25th September 2019) - Mnatzaganian, George; Hiller, Janet E; Braitberg, George; Kingsley, Michael; Putland, Mark; Bish, Melanie; Tori, Kathleen; Huxley, Rachel
Abstract : Objective: To determine whether sex differences exist in the triage, management and outcomes associated with non-traumatic chest pain presentations in the emergency department (ED). Methods: All adults (≥18 years) with non-traumatic chest pain presentations to three EDs in Melbourne, Australia between 2009 and 2013 were retrospectively analysed. Data sources included routinely collected hospital databases. Triage scoring of the urgency of presentation, time to medical examination, cardiac troponin testing, admission to specialised care units, and in-ED and in-hospital mortality were each modelled using the generalised estimating equations approach. Results: Overall 54 138 patients (48.7% women) presented with chest pain, contributing to 76 216 presentations, of which 26 282 (34.5%) were cardiac. In multivariable analyses, compared with men, women were 18% less likely to be allocated an urgency of 'immediate review' or 'within 10 min review' (OR=0.82, 95% CI 0.79 to 0.85), 16% less likely to be examined within the first hour of arrival to the ED by an emergency physician (0.84, 0.81 to 0.87), 20% less likely to have a troponin test performed (0.80, 0.77 to 0.83), 36% less likely to be admitted to a specialised care unit (0.64, 0.61 to 0.68), and 35% (p=0.039) and 36% (p=0.002) more likely to die in the ED and in the hospital, respectively. Conclusions: In the ED, systemic sex bias, to the detriment of women, exists in the early management and treatment of non-traumatic chest pain. Future studies that identify the drivers explaining why women presenting with chest pain are disadvantaged in terms of care, relative to men, are warranted.